Hospice nurses request paediatric-specific educational resources and training programs to improve care for children and families in the community: Qualitative data analysis from a population-level survey. (March 2020) - Kaye, Erica C; Applegarth, Jacob; Gattas, Melanie; Kiefer, Ashley; Reynolds, Jason; Zalud, Kristina; Baker, Justin N
Background: Children with serious illness who receive hospice care often interface with nurses who lack training, experience and comfort in the provision of paediatric palliative and hospice care. Hospice nurse preferences for paediatric-specific training are not well known. Aim: To describe the types of paediatric-specific training received and educational content preferred by hospice nurses. Design: Population-level dissemination of a cross-sectional survey with qualitative analysis of open-ended survey items. Setting/participants: Nurses from 71 community-based hospice organizations across 3 states completed the survey. Results: An open-ended response was provided by 278/551 (50.5%) survey respondents. A total of 55 respondents provided 58 descriptions of prior paediatric-specific training, including a formal 2-day course ( n = 36; 65.5%), on-the-job education ( n = 13, 23.6%), online training ( n = 5, 9.1%), nursing school ( n = 2, 3.6%) and paediatric advanced life support courses ( n = 2, 3.6%). A total of 67 respondents described 74 hospice-led educational efforts, largely comprised of a 2-day course ( n = 39; 54.2%) or provision of written materials ( n = 11; 15.3%). A total of 189 respondents described 258 preferences for paediatric-specific training, with nearly half ( n = 93; 49.2%) requesting 'any' or 'all' types of education and the remainder requesting education around medication use ( n = 48; 25.4%), symptom assessment/management ( n = 32; 16.9%), pain assessment/management ( n = 28; 14.8), communication ( n = 29; 15.3%) and psychosocial assessment/management ( n = 28; 14.8). Conclusions: Hospice nurses self-report inadequate exposure to educational resources and programs, in conjunction with a strong desire for increased paediatric-specific training. Identification of targetable gaps should inform the development of educational resources, policies and other supportive interventions to improve delivery of care to children and families in the community.